Measurement of stress as a function of temperature in Ag and Cu thin films - Proszyński, Adam; Chocyk, Dariusz; Gładyszewski, Grzegorz; Pieńkos, Tomasz; Gładyszewski, Longin (Oficyna Wydawnicza Politechniki Wrocławskiej, 2005)
Stress measurements of 23 nm copper films and 93 nm silver films on Si (100) have been performed during thermal cycling between RT and 450°C. The changes in stress versus temperature are interpreted. The effects of treatment on microstructure and composition are studied by X-ray diffraction.
Optica Applicata, Vol. 35, 2005, nr 3, s. 517-522
Keywords: optyka; annealing; stress measurements; thin films